2021
DOI: 10.1186/s12576-021-00821-1
|View full text |Cite
|
Sign up to set email alerts
|

Diurnal variations in muscle and liver glycogen differ depending on the timing of exercise

Abstract: It has been suggested that glycogen functions not only in carbohydrate energy storage, but also as molecular sensors capable of activating lipolysis. This study aimed to compare the variation in liver and muscle glycogen during the day due to different timing of exercise. Nine healthy young men participated in two trials in which they performed a single bout of exercise at 70% of their individual maximal oxygen uptake for 60 min in the post-absorptive (morning) or post-prandial (afternoon) state. Liver and mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…These data suggest that enhanced maximum speed at ZT21 in mice that experience daily moderate activity is associated with increased selective utilization of carbohydrates for energy production during exercise at ZT21. Consistent with this proposition, a recent study showed that humans exhibit a significantly increased respiratory exchange ratio (RER, a measure of the relative utilization of carbohydrates and fats for energy production) when performing exercise in the afternoon compared to the same exercise performed in the morning [ 27 ]. Similarly, the impact of exercise on lipids, carbohydrates, and other metabolites in several mouse organs depends on the time of day at which exercise is performed [ 28 ].…”
Section: Resultsmentioning
confidence: 90%
“…These data suggest that enhanced maximum speed at ZT21 in mice that experience daily moderate activity is associated with increased selective utilization of carbohydrates for energy production during exercise at ZT21. Consistent with this proposition, a recent study showed that humans exhibit a significantly increased respiratory exchange ratio (RER, a measure of the relative utilization of carbohydrates and fats for energy production) when performing exercise in the afternoon compared to the same exercise performed in the morning [ 27 ]. Similarly, the impact of exercise on lipids, carbohydrates, and other metabolites in several mouse organs depends on the time of day at which exercise is performed [ 28 ].…”
Section: Resultsmentioning
confidence: 90%
“…It is often overlooked that if competition is to be performed in the morning after an overnight fast (or any period of prolonged fasting), liver glycogen stores may be compromised. Namely, in the postabsorptive phase (e.g., during the night) liver glycogen stores decrease [ 41 ]; so, in the morning they can be substantially depleted [ 42 ]. On the contrary, muscle glycogen stores are typically not affected by an overnight fasting period [ 42 ].…”
Section: Importance Of Carbohydrates For Competition and High-intensi...mentioning
confidence: 99%
“…Namely, in the postabsorptive phase (e.g., during the night) liver glycogen stores decrease [ 41 ]; so, in the morning they can be substantially depleted [ 42 ]. On the contrary, muscle glycogen stores are typically not affected by an overnight fasting period [ 42 ]. As numerous competitions start in the morning, it is pertinent that the meals after overnight fast are designed so that there is a focus on liver glycogen repletion.…”
Section: Importance Of Carbohydrates For Competition and High-intensi...mentioning
confidence: 99%
“…For instance, a previous study showed that extreme changes in liver glycogen concentration affect liver T 1 measurements 1 . Given the natural diurnal variation of liver glycogen concentration, 2 these T 1 variations will likely be lower and within the single‐session reproducibility range reported for liver T 1 3 in healthy volunteers and most patients. However, this effect could be exacerbated by impaired glucose metabolism in patients who have T2DM 4 .…”
mentioning
confidence: 98%